(3GdGYJHGQ aj GdJhGQjN hGdGKGQs - (3jhSa Hf MfG GjhH GdMdHj GdeGQhfjs
(3ChdgG (B:s
(3CeG HYO habfi Gddg hEjGc Cf Yde GdJGQjN ef GdYdhe GdLdjdI hMaXg ef GdNUGd GdfHjdI haGFOJg GdGYJHGQ dPhi GdYbhd hGdGHUGQ s
(3BNQgG (B:s
(3hefge Gdabjg GdeYQha Ydi Hf eMeO Hf GdMSf GdeYQha HGHf GdZQjH ai HdGO s
(3HgG fXGe GdJYbjHIs
(3hgh NGU HJGQjN Gdjefs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs